2009
DOI: 10.1021/jm900596y
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Crystallographic and Molecular Dynamics Study of Cathepsin L Retrobinding Inhibitors

Abstract: )These authors contributed equally to the work.Received May 7, 2009 We report the crystal structures of three noncovalent retrobinding inhibitors in complex with mature cathepsin L up to resolutions of 2.5, 1.8, and 2.5 Å , respectively. These inhibitors were Bpa-(Nε-Bpa)-Lys-DArg-Tyr-Npe, Bpa-(Nε-Bpa)Lys-DArg-Phe-Npe, and Bpa-MCys-DArg-Phe-Npe, where Bpa = biphenylacetyl and Pea = N-phenylethyl. These were selected to clarify the binding mode of the biphenyl groups in the S 0 subsites because the addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The authors further investigated the binding mode of this class of inhibitors by means of co-crystal structure and molecular modeling. This revealed that (a) arginine residue of the inhibitor occupied the S1 pocket, (b) phenyl alanine residue found favorable hydrophobic interactions within the S2 pocket, (c) 2-phenylethyl group pointed toward S3 pocket, (d) the methionine residue showed optimal interaction within S1 pocket, and (e) the biphenyl acetyl group extended to the S3 pocket for favorable interactions [95,128]. This class of inhibitors has shown resistance to enzyme-dependent hydrolysis and demonstrates the reversible mode of enzyme inactivation.…”
Section: Propeptide Mimicsmentioning
confidence: 99%
“…The authors further investigated the binding mode of this class of inhibitors by means of co-crystal structure and molecular modeling. This revealed that (a) arginine residue of the inhibitor occupied the S1 pocket, (b) phenyl alanine residue found favorable hydrophobic interactions within the S2 pocket, (c) 2-phenylethyl group pointed toward S3 pocket, (d) the methionine residue showed optimal interaction within S1 pocket, and (e) the biphenyl acetyl group extended to the S3 pocket for favorable interactions [95,128]. This class of inhibitors has shown resistance to enzyme-dependent hydrolysis and demonstrates the reversible mode of enzyme inactivation.…”
Section: Propeptide Mimicsmentioning
confidence: 99%
“…The field is currently focused on the development of reversible cathepsin inhibitors (Wiener et al, 2010). Few peptide-based CatL inhibitors were found reversibly binding to CatL with high potency (K i = 19~45 nM) and selectivity (64~333-fold), compared with CatL’s inhibitions to CatB or CatK (Table 2) (Chowdhury et al, 2002; Shenoy et al, 2009). The most recent CatL-selective and reversible inhibitors are thiocarbazate derivatives (Table 2).…”
Section: Cathepsin Inhibitors In Cardiovascular Diseasesmentioning
confidence: 99%
“…Cathepsin L in complex with propeptide-mimetic reverse binding non-covalent inhibitors has been extensively studied by us (Chowdhury et al, 2002(Chowdhury et al, , 2008Shenoy et al, 2009). The design of these inhibitors is based on the propeptide region of procathepsin L, which is a potent inhibitor of its mature form.…”
Section: Introductionmentioning
confidence: 99%